DAMPAK KEBERADAAN PELABUHAN LINTAS BATAS INTERNASIONAL BANDAR SRI SETIA RAJA TERHADAP PERDAGANGAN HASIL PERKEBUNAN KELAPA PULAU BENGKALIS KE MALAKA - Yuhani, Aulia; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Bengkalis is one of the regions that has access to channel businesses owned by business actors by sea to neighboring countries, namely Malaysia, precisely referred to as the Bandar Sri Setia Raja International Cross Border Port. It is said to be a cross-border port because the port of Bandar Sri Setia Raja breaks through the border between Indonesia and Malaysia with ports located in Bengkalis Regency, Bantan District, the New Strait for the location of loading and unloading ports is in Bengkalis Regency, Bantan District, Teluk Pambang Village, Bloated Luar because large ship owners are in the area making it easier to access.Basically, ports have an important role for the Indonesian population, as well as for the development of industry, both trade and services. This is because the port of Bandar Sri Setia Raja is an important transportation infrastructure for a country, especially maritime like Indonesia, , then the port is also fair in the economy both nationally and regionally so that the existence of this port contributes greatly to the trade of agricultural products on the island of Bengkalis. This research is a qualitative descriptive research that describes descriptive data from phenomena studied with individual analysis units in the community, as well as parties directly related to the Bengkalis International Cross Border Port.The research strategy used is data collection through primary and secondary data with data collection techniques in the form of observation, in-depth interviews and documentation with the aim of obtaining information that is more in line with the research problem. The results of this research show that the existence of the International Cross-Border Port has various impacts on the economy, especially business actors and the community in the Bantan Regency area, Bengkalis. So it provides many changes to the port function which can be seen from several points. . First, the port as an aspect of transportation, which is divided into 3 parts, namely making the port an interface, gateway and industrial estate. Second, ports as an aspect of service where service delivery has a very important and strategic role so that its implementation is controlled by the state and its development is controlled by the government. third, and from the Hinterland Connection aspect, where this aspect is what connects the port with the innermost small areas which have mutual influence and dependence, such as the port will have no meaning if it is not supported by a hinterland which has the potential to develop, especially in the economic sector. It can be concluded that this port plays an important role in the economy of the people of Bengkalis Island. Keywords: Economic Changes, Cross Borders, Business Actors